2017
DOI: 10.1016/s0140-6736(16)32589-2
|View full text |Cite
|
Sign up to set email alerts
|

Guided graded exercise self-help plus specialist medical care versus specialist medical care alone for chronic fatigue syndrome (GETSET): a pragmatic randomised controlled trial

Abstract: SummaryBackgroundGraded exercise therapy is an effective and safe treatment for chronic fatigue syndrome, but it is therapist intensive and availability is limited. We aimed to test the efficacy and safety of graded exercise delivered as guided self-help.MethodsIn this pragmatic randomised controlled trial, we recruited adult patients (18 years and older) who met the UK National Institute for Health and Care Excellence criteria for chronic fatigue syndrome from two secondary-care clinics in the UK. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 28 publications
1
67
0
4
Order By: Relevance
“…[41,44,48,49,51]. In addition, 3 RCTs of graded-exercise-related therapies [52,54,55] and 3 RCTs of integrative, consumer-driven rehabilitation [63], acupuncture [64] and abdominal tuina [66] showed a significantly effect of the intervention compared to the control (Table 3).…”
Section: Rcts With Pharmacological Interventionsmentioning
confidence: 99%
“…[41,44,48,49,51]. In addition, 3 RCTs of graded-exercise-related therapies [52,54,55] and 3 RCTs of integrative, consumer-driven rehabilitation [63], acupuncture [64] and abdominal tuina [66] showed a significantly effect of the intervention compared to the control (Table 3).…”
Section: Rcts With Pharmacological Interventionsmentioning
confidence: 99%
“…This study sought to understand the experiences of guided graded exercise self-help delivered as part of an RCT. In particular, we compared experiences, perspectives and approaches of those who were "much better" or "a little worse" after the 12 week programme [17]. Our findings revealed similarities between the "much better" and "a little worse" groups in their experiences and approaches to GES: many found doing GES challenging, and personal motivation played a key role in participants sticking with their GES programmes.…”
Section: Key Findingsmentioning
confidence: 90%
“…This qualitative, one-to-one interview study was situated within a pragmatic RCT of GES; which found that GES was moderately better than SMC at reducing fatigue and improving functioning [17]. This design was chosen because narratives from interviews provide an overarching 'code' for the way people construct -and then communicate -meanings about themselves [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящее время в лечении СХУ доказана эффективность когнитивно-поведенческой психотерапии, некоторых антидепрессантов, дозированной физической нагрузки [16][17][18][19][20].…”
Section: Introductionunclassified